Colocation opportunities for large solar infrastructures and agriculture in drylands. (1st March 2016) - Ravi, Sujith; Macknick, Jordan; Lobell, David; Field, Christopher; Ganesan, Karthik; Jain, Rishabh; Elchinger, Michael; Stoltenberg, Blaise
Graphical abstract: Highlights: We explored the potential to colocate solar installations and agriculture. Water use at solar installations are similar to amounts required for desert plants. Co-located systems are economically viable in some areas. Colocation can maximize land and water use efficiency in drylands. Abstract: Solar energy installations in arid and semi-arid regions are rapidly increasing due to technological advances and policy support. Although solar energy provides several benefits such as reduction of greenhouse gases, reclamation of degraded land, and improved quality of life in developing countries, the deployment of large-scale renewable energy infrastructure may negatively impact land and water resources. Meeting the ever-expanding energy demand with limited land and water resources in the context of increasing demand for alternative uses such as agricultural and domestic consumption is a major challenge. The goal of this study was to explore opportunities to colocate solar infrastructures and agricultural crops to maximize the efficiency of land and water use. We investigated the energy inputs/outputs, water use, greenhouse gas emissions, and economics of solar installations in northwestern India in comparison to aloe vera cultivation, another widely promoted and economically important land use in these systems. The life cycle analyses show that the colocated systems are economically viable in some rural areas and may provide opportunities for rural electrification and stimulate economic growth. The water inputs for cleaning solar panels are similar to amounts required for annual aloe productivity, suggesting the possibility of integrating the two systems to maximize land and water use efficiency. A life cycle analysis of a hypothetical colocation indicated higher returns per m 3 of water used than either system alone. The northwestern region of India has experienced high population growth in the past decade, creating additional demand for land and water resources. In these water-limited areas, coupled solar infrastructure and agriculture could be established in marginal lands with low water use, thus minimizing the socioeconomic and environmental issues resulting from cultivation of economically important non-food crops (e.g., aloe) in prime agricultural lands.